(untitled) (The Planet, 2023)
Objective: In this study, our main goal is to evaluate andcomparethe LVEF of acute anterior & inferior wall MI &their early hospital outcome. Method: From April 1, 2022,through March 31, 2023, researchers from the cardiologydepartment at MMCH in Mymensingh, Bangladesh,conducted a cross-sectional study. This was a researchwhere 120 hospitalized individuals with AMI may takepart. The fourth global definition of myocardial infarctionwas used to establish the criteria for diagnosing an AMI. Atotal of 60 patients were included in the study: 20 withanterior MI (n=23 with complications) and 40 with inferiorMI (n=16 with complications; n=44 withoutcomplications). Results: Patients older than 50 made upthe bulk of the sample in this study, with malepredominance in both groups, Moreover, the prevalencetobacco use, type 2 diabetes, high blood pressure, abnormal lipid profiles, and BMI are morecommon incomplicated groups. Reduced LVEF and LV failure was found more in AnteriorMI, (35%)& (30%) whereas in inferior MI it was seen in (25%)& ( 16.67%) respectively. Butmechanical complication (Ischemic MR) was seen more in Inferior MI (25%) than Anterior MI (18.33%) similarly Arrhythmia was found higher in inferior the MI group (20% )thananterior MI group ( 5%). No death case was noticed between the two groups. Conclusion:Based on our results, we can say that LVEF is more affected in superior MI in the front to MIin the back and so Left ventricular failure as a complication of MI is more prevalent in acuteanterior MI, whereas mechanical complication (Ischemic MR) & arrhythmia was seen morein Inferior MI.